Umumta‘lim maktab rahbarlarida vaqtni boshqarish kompetentligini rivojlantirish muammolari - Bekniyazov, B.S (SCIENCE and SOCIETY, 2024)
The article presents the results of a survey and interview on the use of time in everyday life and at work by managers and teachers of secondary schools. As a result of the study, the author made recommendations and suggestions for the effective use of time in the teaching activities of teachers.
Keywords: time-management; pedagogic worker; planning; urgent and important objectives; procrastination; timeabsorbers